ALIH KODE DAN CAMPUR KODE OLEH MASYARAKAT DAYAK BANYUKE-SAKANIS DIALEK BANANA"™ DI DESA SEMAYANG - Marpaung, Marpaung; Patriantoro, Patriantoro; Seli, Sesillia; Simanjuntak, Hotma; Wartiningsih, Agus (Jurnal Kajian Pembelajaran dan Keilmuan, 2023)
The purpose of this research is to describe the code switching and code mixing of the Banyuke-Sakanis Dayak language, Banana"™ dialect, in Semayang Village from the perspective of sociolinguistic theory. The research approach used in this study is a qualitative approach that employs systematic methods. The code switching and code mixing of the Banyuke-Sakanis Dayak language, Banana"™ dialect, in Semayang Village, involve the phenomena of shifting and mixing between the Banana dialect, Bisomu language, Banyadu language, and Indonesian language. The Banana"™ dialect serves as B-1, while the Bisomu language, Banyadu language, Indonesian language, and elements of the English language serve as B-2. This process occurs due to the environmental factors of the research object, which is predominantly a bilingual and even multilingual family-based community. Code switching and code mixing are common linguistic phenomena experienced by speech communities during interactions. The community experiencing these phenomena is examined using sociolinguistic theory, as there is a close relationship between language phenomena and the community. Sociolinguistics discusses language from a societal perspective, while code switching and code mixing are among the phenomena that occur in speech communities. Data collection in this research uses the technique of observation through the method of note-taking. Once the data is obtained, the next step is data analysis.